Chemistry : - Spencer, James N. (Wiley, 2012)
Developed in conjunction with the ACS Task Force on the General Chemistry Curriculum Core themes emphasis -- process of science, relationship between molecular structure and physical/chemical properties, and relationship between micro and macro levels Based on a hands-on approach to learning chemistry